2008
DOI: 10.1093/ndt/gfn571
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular calcification in long-haemodialysis patients: associated factors and survival consequences

Abstract: A plain radiological score showed the high prevalence (83%) of VCs in HD patients in spite of a long and intensive dialysis strategy and adherence to guidelines. The main associated factors were classic factors such as ageing and diabetes. No relationship was found with blood pressure and phosphataemia that remained well controlled in long dialysis; the association with FGF-23 serum levels may aggregate some non-traditional risk factors. The harmful effects of VCs on survival require their systematic assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
144
4
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(170 citation statements)
references
References 43 publications
17
144
4
5
Order By: Relevance
“…Furthermore, among the mineral metabolites we tested, FGF23 was most strongly correlated with each inflammatory marker, and FGF23 but not PTH or phosphate was associated with greater odds for severe inflammation in multivariable models. Given the associations between inflammation, atherosclerosis, and vascular calcification (21), and that some studies have shown association between elevated FGF23 and calcification in CKD and ESRD (22,23), these results provide new insight into another potential mechanism underlying the strong associations between elevated FGF23, cardiovascular disease, and mortality. Further studies are needed to determine whether FGF23 might contribute to atherosclerosis and vascular calcification by stimulating inflammation or whether inflammation might contribute to the development of vascular disease through effects on FGF23.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, among the mineral metabolites we tested, FGF23 was most strongly correlated with each inflammatory marker, and FGF23 but not PTH or phosphate was associated with greater odds for severe inflammation in multivariable models. Given the associations between inflammation, atherosclerosis, and vascular calcification (21), and that some studies have shown association between elevated FGF23 and calcification in CKD and ESRD (22,23), these results provide new insight into another potential mechanism underlying the strong associations between elevated FGF23, cardiovascular disease, and mortality. Further studies are needed to determine whether FGF23 might contribute to atherosclerosis and vascular calcification by stimulating inflammation or whether inflammation might contribute to the development of vascular disease through effects on FGF23.…”
Section: Discussionmentioning
confidence: 83%
“…In patients with CKD, FGF23 levels are thought to increase as a compensatory response to maintain normal P balance, because the capacity for renal P excretion declines (8). Recent studies indicate that increased levels of FGF23 are associated with mortality, CKD progression, and calcification in CKD patients (9)(10)(11)(12). These evidences suggest that early treatment of calcium-phosphate alterations may lead to improved management of CKD progression and associated CV complications.…”
Section: Introductionmentioning
confidence: 99%
“…49 In addition to the possible relations between FGF-23, CKD progression, hyperparathyroidism, ventricular hypertrophy, and mortality, high FGF-23 levels are believed to correlate with vascular calcification. 50,51 Our group studied, for one year, 72 patients undergoing hemodialysis and found a positive correlation between FGF-23 levels and the vascular calcification score assessed by use of coronary tomography in the group of patients treated with sevelamer hydrochloride. 52 dIscussIon An important question that remains unanswered relates to the possible existence of other actions of FGF-23, whether that hormone is only an indirect marker of toxicity of other factors, like P, or whether it has a direct toxic effect on vascular endothelium and renal tissue.…”
Section: Fgf-23 and Clinical And Experimental Studiesmentioning
confidence: 94%